Performance testing of steam ejector air conditioning system - Ong, Soon Beng. (2009)
With the increasingly concern on energy efficiency and environmental friendliness, scientists and engineers all over the world are reaching out to fuel conservation, waste heat utilization, cost reduction and reduction in pollution level which damages the planet.